Biological Protective Effects Against Vibrio Infections in Grouper Larvae Using the Strombidium sp. NTOU1, a Marine Ciliate Amenable for Scaled-Up Culture and With an Excellent Bacteriovorous Ability - Lin, Hung-Yun; Yeh, Wei-Yu; Tsai, Sheng-Fang; Chiang, Kuo-Ping; Lin, John Han-You; Tsao, Che-Chia; Lin, Han-Jia (Frontiers in Marine Science, 2020)
Bacterial infectious diseases cause a huge economic loss in aquaculture. Active biological control that uses bacterivorous organisms to remove pathogens is an ecologically friendly approach for the cultural system to counteract the bacterial infection. The ciliate is one of the main predators of bacteria in aquatic ecosystems, but whether it can be effectively adopted to protect aquaculture organisms from bacterial pathogens still remains to be investigated. In this study, we optimized the culturing method for a marine ciliate Strombidium sp. NTOU1 and analyzed its bacterivorous properties. Strombidium sp. NTOU1 could feed on a variety of bacteria including pathogenic species. By controlling the amount of frozen bacteria Erwinia spp. in the medium, the ciliate grew to the maximum density within 4 days and could reach 1.2 x 105 cells/mL after the suction filtration enrichment. Ingested bacteria were observed in the food vacuole of the ciliate, and the average bacterial clearance rate of a single NTOU1 cell was ~300 cells/hr. In the challenge trial which grouper larvae were exposed to an extreme environment containing a high density of the pathogen Vibrio campellii, only 33% of the grouper larvae could survive after 5 days. However, preincubating with Strombidium sp. NTOU1 for an hour resulted their survival rate to rise to 93%. Together, our results demonstrated that Strombidium sp. NTOU1 has the potential to become a biological control species to actively remove pathogens in aquaculture. In addition, the technical improvement to culture Strombidium sp. NTOU1 provides an advantage for this ciliate in the future academic research or biotechnological application.